Hanefi fetva usulünün teşekkülü ve IV.-X. yy. arası teori-pratik ilişkisi - Büyükmutu, Mehmet (My University, 2024)
Hanefi Fetva Usulünün Teşekkülü ve IV.-X. YY. Arası Teori-Pratik İlişkisi isimli bu çalışma, kavramsal ve kurumsal olarak fetvâ usûlü doktrinin ilerlemesini mercek altına almayı hedefleyen bir muhtevaya sahiptir. İlk bölümde, bir süreye kadar fetvâ ile aynı manada kullanılan ictihad ve kadâ ifadelerinin fetvâdan metodoloji olarak ayrılmasına, fetvâ usûlünü yakından ilgilendiren mezhep, taklit, tahrîc, tercih ve nevâzil kavramlarının muhteva ve tarihsel arka planına temas edilmektedir. İkinci bölüm fetvâ usûlünün tanım, muhteva, gaye ve muhatabına, dönemsel olarak fetvâ usûlünün oluşum ve gelişimine, IV. hicrî asırdan ilk müstakil Hanefî fetvâ usûlü eserinin telif edildiği X. hicrî asra kadarki süreçte fetvâ usûlü kâideleri ile ahlâkî hususlara detaylı şekilde temas etmekte ve her bir dönemi, barındırdığı farklılık ve gelişmeleri, bir önceki dönem ile mukayese ederek dönemsel özgünlükleri ortaya koymaktadır. Üçüncü bölümde ise fetvâ usûlü kâideleri, belirli bir tema çerçevesinde kâide gruplarına ayrılarak ilk dönemden itibaren ilgili kâidenin hangi dönemde nasıl bir gelişme gösterdiği ve son tahlilde neye evrildiği incelenmektedir. Bu çerçevede söz konusu kâidelerin Hanefî furû-ı fıkhına nasıl yansıdığı ve ne şekilde kullanıldığına dair örneklere yer verilmekte, kâideler misallerle açıklanmaya çalışılmaktadır.

This study, titled The Formation of Hanefî Fatwa Methodology and the Theory-Practice Relationship from the 4th to the 10th Century, examines the formation and development of fatwa methodology from both conceptual and institutional perspectives. The first section provides a detailed analysis of how the terms ijtihad and qada, which were used interchangeably with fatwa up to a certain period, were distinguished from fatwa in methodological terms. Additionally, it explores the content and historical background of concepts closely related to fatwa methodology, such as madhhab, taqlid, tahrij, preference, and nawazil. The second section addresses the definition, content, purpose, and addressees of fatwa methodology, and analyzes its formation and development over time. This includes a detailed examination of the progress of fatwa rules and ethical issues from the 4th Hijri century up to the 10th Hijri century, when the first independent Hanefî fatwa methodology work was authored. Each period is compared with the previous one to highlight its unique characteristics and developments. The third section focuses on fatwa rules and their reflections on Furu' al-fiqh (fatwas and ijtihads). In this context, fatwa rules are categorized into thematic groups, and the development of each rule from the early period is examined, shedding light on its periodical advancements and the conclusions reached in the present day. Examples are also provided to illustrate how these rules have been reflected in Hanefî fiqh and how they have been applied.
The formation of the Hanafi fatwa method and revelance between practive and theory in the IV.-X. century
Keywords: Abu'l-Lays al-Samarqandi; Âdâbü'l-Fetvâ; Badr al-Din al-Shuhawi; Bedreddin eş-Şuhâvî; Ebü'l-Leys es-Semerkandî; Edebü'l-Müftî; Extraction or Deduction (of legal rulings); Fatwa Methodology; Fatwas; Fetvâ Usûlü; Fetvâ Usûlü Literatürü; Fetvalar; Hanefî Mezhebi; Hasiri; Hasîrî; Independent Legal Reasoning; Islamic law; İctihad; İslam hukuku; Judicial Ruling; Kadâ; Kâdîhân; Literature of Fatwa Methodology; Muhammad al-Dastinai; Muhammed ed-Destinâî; Müftâ bih; Qadi Khan; Resmü'l-Müftî; Sadr al-Shahid; Sadruşşehîd; Tahrîc; The Etiquette of Fatwa; The Etiquette of the Mufti; The Hanafi School of Law; The Official Conduct of the Mufti; The Ruling Preferred by the Mufti